OPTIMASI JUMLAH EGG REPLACER DAN PENGARUHNYA TERHADAP KARAKTERISTIK EGG-FREE MAYONNAISE PROBIOTIK - Novia Hidayati Inasa; Faradhilla Dewi Rosanti; Rafli Zulfa Kamil; Antonius Hintono (AGROINTEK, 2024)
Mayonnaise is an oil in water (O/W) semi-solid emulsion that is widely used in the food industry as salad dressing, sauce, and condiment. The use of eggs in the production of mayonnaise was considered health concerns for some people. This study aimed to determine the effect of egg replacer on the physical, chemical, microbiological and organoleptic properties of egg-free probiotic mayonnaise. This study used one-factor Completely Randomized Design (CRD) with variation treatment of egg replacer were 0% (P0), 5% (P1), 10% (P2), 15% (P3) and, 20% (P4). Variables observed included: pH value, amount of lactic acid bacteria, viscosity, stability, droplet size, moisture content, fat content, and organoleptic. The parametric data obtained were analyzed using Analysis of Variance (ANOVA), non-parametric data were analyzed using Kruskall Wallis test, and the droplet size were described descriptively qualitatively. The result of the study showed that the optimal amount of egg replacer was at concentration of 10% (P2) that showed 2,88 on pH value; 7,39 log of Lactic Acid Bacteria, 17.775 cP on viscosity, 89,88% on stability, 32,64% moisture contents, 53,56% fat content, small and uniform droplet size, slightly yellow color, slightly sweet taste, creamy texture, and slightly soy flavor. The amount of egg replacer had a significant effect (p0,05) to increased pH value, total LAB, viscosity, stability, moisture content and decreased the droplet size, fat content, and organoleptic of the egg-free probiotic mayonnaise.